O papel dos movimentos sociais na formulação de políticas públicas para população atingida por barragens e mineradoras: um estudo fundamentado no modelo de múltiplos fluxos - Oliveira, Camilo José da Rosa (2018)
Movements of popular participation have always played a relevant role as agents of pressure and political interference on requiring better life conditions, including the struggle for human rights, equality, protection, etc. In Brazil, especially after the period of re-democratization along side with the Federal Constitution, several rights were achieved and social movements gained even more space and also new shapes. The creation of public politics that materializes established rights, which also may be effective upon improving life conditions of the population, is still an immediate goal of organized social groups. With the economic development on the last decades, great economic venture implementations were expanded, reaching countless people. Mining companies and electric energy production barrages have been causing great impact on local communities. Therefore, we highlight the Affected by Barrages Movement (MAB, in Portuguese) and the Popular Sovereignty in Mining Movement (MAM, in Portuguese) on the struggle for rights of the affected population and as main articulation and political influence movements on the creation of public politics that can meet the demands of the affected ones. Therefore, this study aimed to understand, without the intention of burning out the subject, the actions embraced by the Affected by Barrages Movement (MAB) and the Popular Sovereignty in Mining Movement (MAM) to influence on the process of creating public politics for the affected by barrages and mining companies ones, from an analysis based on the Kingdon model. Three studies were conducted: the first one aimed to describe the role of social movements on creating public politics; the second one aimed to understand the problems and solutions according to the Kingdon model through the issues of MAB and MAM and demands by the people affected by the barrages and mining activities; and the third study aimed to understand the political flux according to Kingdon, from actions embraced by the MAB and the MAM. Both articles were written based on the multiple flux analysis model proposed by Kingdon (1984), which guides the formulation of the governmental agenda from the confluence of problems and political solutions. Based on these studies, it was noticed that there are connections between the actions developed by both movements with the proposals made by Kingdon and that practice allows to influence on the creation of the governmental agenda, in spite of not being based on a linear process and having certain results, since there are other interests competing for space on the agenda.